The Way in which Philosophy Extends to Include Sciences in the Islamic Philosophy with an Emphasis on Ayat Allah Javadi Amoli’s Exposition - Ali Latifi (حکمت اسرا)
The principal problem in the present study is to answer the following question: how philosophy, according to Islamic philosophers, extends to the sciences referring to life and how philosophy contribute to the production and reproduction of scientific theories. With aids of an analytic-descriptive method and by reading out the topics in the Islamic philosophy referring to the philosophy and sciences relations (with especial attention to Ayat Allah Javadi Amoli’s exposition), we try first to describe the most important features of Islamic philosophy views about the relation between philosophy and sciences and then with a logical analysis we will say the points of this view, its implications, its capacities, and the new horizons it opens in the way in which philosophy extends to sciences. The distinction criterion in sciences, the subject-matters of philosophy and sciences and their relation, the status of subject-matter, elements and problems in sciences and their relation with each other are among the most important problems in Islamic philosophy which make an appropriate framework for investigating the way in which philosophy extends to sciences; these topics will be discussed in the section on ‘reading out’. In the final section the most important implications and capacities of this readout for the way in which philosophy could contribute to the production and reproduction of scientific theories will brought out in form of five fundamental principles: the contribution of philosophy to providing premises necessary for establishing some of the scientific problems, emphasis on the scientist proficiency over his/her principles of philosophical knowledge, the role this proficiency plays in theoretical deepening and argumentative accuracy of theories, and also a true interpretation of the term ‘additional philosophies’ according to Islamic philosophy.